Identification of a Torque Teno Mini Virus (TTMV) in Hodgkin’s Lymphoma Patients - Pan, Shaokun; Yu, Tian; Wang, Yanchun; Lu, Renquan; Wang, Huijie; Xie, Youhua; Feng, Xiping (Frontiers in Microbiology, 2018)
At least twelve percent of human cancers are caused by virus infection. To understand whether other viruses are associated with human cancers, a viral metagenomics approach was used to analyze the composition of the viral communities of the serum of the patients with Hodgkin’s lymphoma and Non-Hodgkin lymphoma. In this report, a human anellovirus TTMV named TTMV-SH was discovered from three patients with Hodgkin’s Lymphoma. The complete genome of TTMV-SH is 2812nt in length. Phylogenetic analysis based on ORF1 indicated that TTMV-SH of the 11 isolates cluster with TTMV strain TLMV-CBD231 sharing only 60.3%-62% sequence similarity, and the sequences divergence is 41.5%-43.1%, which indicates that TTMV-SH is a novel species. The TTMV-SH prevalence in HL group, especially in nodular sclerosing Hodgkin's lymphomas (NCHL), was significantly higher than in the healthy group implicated that the TTMV-SH may be associated with Hodgkin’s lymphoma, especially NCHL.